Analysis of Defects in the Poetic Eloquence Children - Ramin Moharami; Khodabakhsh Asadollahi; Shokrallah Pouralkhas; payam foroghirad (مطالعات زبانی و بلاغی)
Poem, in spite of the fact that develops individual and social aspects of child’s life, aesthetic taste, emotional and lexical richness, may result in negative effects in his linguistic performance. Deviations from ordinary standards of language, inappropriate application of words and ill-formed sentences structures cause mal-substitution of grammatical constructions in child’s lexicon. However, poets are considered not to disregard linguistic elements at the expense of acquiring musical elements. In this connection, rhetoric, and then poetics must be ranked in the first place. In order for the discourse and the situational context of the addressee aptly met, it seems necessary to choose linguistic patterns with respect to the age group of the addressees. This makes children to perceive plain language easily. The use of adult language in child poetry complicates its perception and diminishes its eloquence quality. Opacity of terms, semantic and syntactic ambiguities, and hyperboles are the major pitfalls of child poems. In the current study, it is aimed to study the type of the mentioned pitfalls. The necessity of the present research lies in applicability of its results, paying much more attention to the ways of language application in child poems and preventing losses in child’s language.